1907 N.H. Laws 142, An Act Relating to the Committing of Burglary with Explosives, ch. 146, §§ 1-4. - (:unkn) unknown (General Publisher, 1907)
Provided that any person who breaks and enters a building with gunpowder, nitroglycerine, dynamite, or other explosives and commits burglary will be deemed guilty of burglary with explosives
--
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME